Mengidentifikasi Kebutuhan Sistem Penerimaan Mahasiswa Baru Dalam Penerapan Blockchain Pada Universitas Bina Darma Palembang - Muhammad Iqbal Sidiq; Darius Antoni (Jurnal Pengembangan Sistem Informasi dan Informatika, 2021)
The development of an era that is increasingly sophisticated makes us have to keep up with the times, especially since we will enter the era of the industrial revolution 4.0, where almost all activities use technological systems that help and facilitate people in everyday life. Likewise with an educational institution that must keep up with the current developments. There are so many technological systems that have emerged today and one of the systems is Blockchain. Blockchain is a technology system for recording digital transaction data that is connected through cryptography managed by a group of computers, Blockchain is very helpful because transactions are made easier because they no longer require intermediaries. Looking at the Blockchain itself, it feels quite right to be applied on campus, because one of the advantages of Blockchain is that it is transparent, where every data transaction is carried out without the intervention of others without third parties, this technology is easy to cost, low cost and fast transactions.